2022
DOI: 10.1101/2022.06.09.495066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Angelman syndrome patient neuron screen identifies a potent and selective clinical ASO targeting UBE3A-ATS with long lasting effect in cynomolgus monkey

Abstract: Angelman syndrome (AS) is a severe neurodevelopmental disorder caused by the loss of neuronal E3 ligase UBE3A with no available treatment. Restoring UBE3A levels via downregulation of the paternally cis-acting long non-coding antisense transcript (UBE3A-ATS) is a potentially disease modifying. Developing molecules targeting human UBE3A-ATS is challenging because its expression and function is restricted to neurons and lacks species sequence conservation. To overcome this, we performed a library screen of locke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…This suggests that there might be a discrepancy between the levels of RNA expression and protein function for TS rescue. Consistent with this, one recent ASO study found that a highly efficient knockdown of UBE3A-ATS was required to elevate the Ube3a protein level, yet UBE3A protein continued to increase with higher ASO concentrations even when mRNA restoration plateaued 29 .…”
Section: Aso Exposure Rescues Delayed Channel Inactivation and Intern...mentioning
confidence: 57%
“…This suggests that there might be a discrepancy between the levels of RNA expression and protein function for TS rescue. Consistent with this, one recent ASO study found that a highly efficient knockdown of UBE3A-ATS was required to elevate the Ube3a protein level, yet UBE3A protein continued to increase with higher ASO concentrations even when mRNA restoration plateaued 29 .…”
Section: Aso Exposure Rescues Delayed Channel Inactivation and Intern...mentioning
confidence: 57%